Length-weight relationship in Rasbora daniconius (Ham.) from Achancoil river, Pathanamthitta, Kerala, India - Sunil, M S (Indian Journal of Fisheries, 2011)
The relationship between length and weight in fishes is generally curvilinear.Length-weight studies in the adults and juveniles of Rasbora daniconius fromSeptember 1995 to February 1996 from Achencoil river near Pathanamthittaindicate that the relationship is significant and they show allometric growthpattern.